2021
DOI: 10.1186/s12964-021-00753-8
|View full text |Cite
|
Sign up to set email alerts
|

JMJD3: a critical epigenetic regulator in stem cell fate

Abstract: The Jumonji domain-containing protein-3 (JMJD3) is a histone demethylase that regulates the trimethylation of histone H3 on lysine 27 (H3K27me3). H3K27me3 is an important epigenetic event associated with transcriptional silencing. JMJD3 has been studied extensively in immune diseases, cancer, and tumor development. There is a comprehensive epigenetic transformation during the transition of embryonic stem cells (ESCs) into specialized cells or the reprogramming of somatic cells to induced pluripotent stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 110 publications
0
12
0
Order By: Relevance
“…To do that, SMAD2/3, the major effectors of the pathway, cooperate with specific cofactors to regulate transcription. Particularly, SMAD3 interacts with the lysine demethylase (KDM) JMJD3 23 , 27 , 28 , a Jumonji C (JmjC) domain-containing enzyme that catalyzes the histone 3 lysine 27 trimethylation (H3K27me3) removal 29 , 30 and has been linked to numerous developmental processes (reviewed in 31 , 32 ). In cortical progenitor cells, we have previously shown that JMJD3 cooperates with the TGFβ pathway to induce neuronal differentiation 23 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…To do that, SMAD2/3, the major effectors of the pathway, cooperate with specific cofactors to regulate transcription. Particularly, SMAD3 interacts with the lysine demethylase (KDM) JMJD3 23 , 27 , 28 , a Jumonji C (JmjC) domain-containing enzyme that catalyzes the histone 3 lysine 27 trimethylation (H3K27me3) removal 29 , 30 and has been linked to numerous developmental processes (reviewed in 31 , 32 ). In cortical progenitor cells, we have previously shown that JMJD3 cooperates with the TGFβ pathway to induce neuronal differentiation 23 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of human monocytes trained by exposure to β-glucan showed that they accumulate fumarate (a metabolite of tricarboxylic acid cycle (TCA)), which downregulates histone demethylase KDM5. Another TCA metabolite, the αketoglutarate, mediates epigenetic reprograming through the histone demethylase Jumonji domain-containing protein-3 (JMJD3) that regulates trimethylation of histone H3 on lysine 27 [60,75].…”
Section: Molecular Signature and Markers Of Memory Monocytes/macrophagesmentioning
confidence: 99%
“…However, little information is available about the underlying mechanism of MALAT1 in regulating the odontoblastic differentiation of hDPSCs. Jumonji domain‐containing 3 (JMJD3) is a histone demethylase with substrate specificity for catalysing the removal of histone 3 lysine 27 trimethylation (H3K27me3), which is a gene silencing mark (Ding et al, 2021). Several studies have demonstrated that JMJD3 promotes odontogenic differentiation by removing H3K27me3 silencing marks on differentiation‐related gene promoters in dental‐derived MSCs (Hoang et al, 2016; Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%